2017
DOI: 10.1002/adfm.201606526
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Carbon Nanotube Auxetic Rubber Bionic Composites with Negative Variation of the Electrical Resistance and Comparison with Their Nonbionic Counterparts

Abstract: Microorganism metabolic activity can facilitate the formation of cellular material systems that have unusual mechanical and physical properties. In the living world microorganisms are commonly used for preparing porous food by fermentation; here carbon nanotubes, graphene nanoplatelets, and a mix of them are dispersed in liquid silicone rubber with single-cell fungi of commercial beer yeast. The fermentation of such microorganisms during the gelling of the silicone matrix results in bionic composites with buck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…In these bionic materials, both the living cells and the carbon materials contribute synergistically to the final properties of the materials. Finally, a recent example of a graphene, CNT, and liquid rubber composite produced through yeast fermentation was reported . CO 2 bubbles produced during fermentation along with collapsed yeast cells resulted in the transformation of conventional silicone rubber composites to auxetic robust rubber.…”
Section: Composite Elm Materialsmentioning
confidence: 99%
“…In these bionic materials, both the living cells and the carbon materials contribute synergistically to the final properties of the materials. Finally, a recent example of a graphene, CNT, and liquid rubber composite produced through yeast fermentation was reported . CO 2 bubbles produced during fermentation along with collapsed yeast cells resulted in the transformation of conventional silicone rubber composites to auxetic robust rubber.…”
Section: Composite Elm Materialsmentioning
confidence: 99%
“…In the case of graphene sheets the bionic composite showed again a higher failure strength, and was able to self-repair after placing the composite material containing living yeast cells back into growth medium. 9 Finally, a recent example of a graphene, CNT, and liquid rubber composite produced through yeast fermentation was reported: 38 Poisson's ratio (i.e., the so called auxetic behavior) that will contract (expand) in the transverse direction when compressed (stretched). 39 Such materials may find in perspective practical applications; for example, once infiltrated in a cavity with a smaller dimension auxetic materials can be used as swell tools that expand by means of tensile stress to conform to the wellbore and to remain anchored to it.…”
Section: Yeasts and Bacteria As Microfactories For Engineering Nanomamentioning
confidence: 99%
“…Recently, the synergistic properties of NBR/CNTs/GNPs and ethylene-propylene-diene terpolymer rubber/carbon black/GNPs nanocomposites have been explored (Valentini et al, 2016(Valentini et al, , 2017(Valentini et al, , 2018. It was found that the combined effect of CNTs/GNPs hybrid filler, exhibited astonishing improvements in terms of mechanical properties, barrier properties, and thermal conductivity.…”
Section: Addressing the Challengesmentioning
confidence: 99%
“…Rubber-like materials are those that once compressed along an axis expand in directions orthogonal to the applied load (e.g., positive Poisson's ratio) being the Poisson's ratio values for the majority of them about 0.5. Designed mechanical instabilities on soft materials have been used to realize materials with a negative Poisson's ratio (i.e., the so called auxetic behavior) that will contract (expand) in the transverse direction when compressed (stretched) (Bertoldi et al, 2010;Valentini et al, 2017). Such materials may find in perspective practical applications; for example, once infiltrated in a cavity with a smaller dimension auxetic materials can be used as swell tools that expand by means of tensile stress to conform to the wellbore and to remain anchored to it (Mody et al, 2013).…”
Section: Counterintuitive Solutionsmentioning
confidence: 99%